A chiral metal‐organic framework core‐shell microspheres composite for high‐performance liquid chromatography enantioseparation. Issue 21 (16th September 2021) - Chen, Ji‐Kai; Xu, Na‐Yan; Guo, Ping; Wang, Bang‐Jin; Zhang, Jun‐Hui; Xie, Sheng‐Ming; Yuan, Li‐Ming
Abstract: The unique features of uniform and adjustable cavities, abundant chiral active sites, and high enantioselectivity make chiral metal‐organic frameworks popular as an emerging candidate for enantioselective separation. However, the wide particle size distribution and irregular shape of as‐synthesized metal–organic frameworks result in low column efficiency, undesired chromatographic peak shape, and high column backpressure of such metal–organic frameworks packed columns. Herein, we report the fabrication of chiral core‐shell microspheres [Cu2 (d ‐Cam)2 (4, 4′‐bpy)]n @SiO2 composite for high‐performance liquid chromatography enantioseparation to overcome the above‐mentioned problems. The [Cu2 (d ‐Cam)2 (4, 4′‐bpy)]n @SiO2 packed column gave high‐resolution separation of racemates under low column backpressure (10‐22 bar), indicating its synergistic effect of the good column packing property of the SiO2 microspheres and the chiral recognition ability of [Cu2 (d ‐Cam)2 (4, 4′‐bpy)]n crystals. Thirteen kinds of chiral compounds including alcohols, amines, ketones, epoxides, and organic bases were well separated with good peak shapes and high column efficiency (18200 plates/m for 1‐(9‐anthryl)‐2, 2, 2‐trifluoroethanol) on the [Cu2 (d ‐Cam)2 (4, 4′‐bpy)]n @SiO2 packed column. Among them, seven pairs of enantiomers achieved baseline separation and the resolution value for 1‐(9‐anthryl)‐2, 2, 2‐trifluoroethanol reached 11.22. Some effects such as column temperature, and analytes mass on the enantioseparations have been investigated. In addition, the [Cu2 (d ‐Cam)2 (4, 4′‐bpy)]n @SiO2 packed column exhibited good stability and repeatability for the separation of chiral compounds. The relative standard deviations for five replicate separations of 1‐phenylethanol were less than 1.0, 1.5, 3.0, and 2.0% for the retention time, peak area, number of theoretical plates, and resolution, respectively. The research results demonstrated the development of chiral metal–organic frameworks core‐shell microspheres composite provide a promising platform for their practical application in chiral separation fields.